Crack control design due to drying shrinkage in restrained reinforced concrete wall. (21st October 2011) - Chung, Lan; Lee, Moon‐Sung; Seo, Tae‐Seok
SUMMARY: This study considered the crack control design method of reinforced concrete wall subjected to uniaxial tension caused by drying shrinkage. From this study, a practical crack control design method of RC wall by controlling the restraint tensile strain caused by drying shrinkage was proposed. In addition, the validity of the proposed method was investigated by comparing with the experimental results (restraint ratio and restraint tensile strain) of small‐scale RC wall specimens under the uniaxial restrained condition. In conclusion, there was good agreement between the values predicted by the proposed method and the experimental values. It is expected that the method proposed in this study enables quantitative crack control design through rational combinations between the materials and structural design. Copyright © 2011 John Wiley & Sons, Ltd.